(untitled) (Revista Apotheke, 2022)
This article is an account of my trajectory as an artist/professor at the Universidade Regional do Cariri and at the Universidade Federal do Piauí, which, through craftsmanship, focusing on textile processes, have been proposing new possibilities for creation and artistic references. Since I graduated, my work has been experimenting with materials and manual processes such as sewing and embroidery, which gained strength during my master’s degree when I got in touch with the Associação das Bonequeiras no Pé de Manga, who work with rag dolls at city ​​of Crato-CE, I came to understand handcraft as art. Since I took up teaching in 2019, I have been provoking my students to look at their own territory, at references that are outside the academy and are part of local popular culture. Based on the research by Ivone Richter (2008) which became my main reference in this research, this article aims to report on the use of popular knowledge at the University and how students appropriate this knowledge.